Evaluation of a Programming Algorithm for the Third Tachycardia Zone in a Fourth-Generation Implantable Cardioverter-Defibrillator - Neglia, John J.; Krol, Ryszard B; Giorgberidze, Irakli S; Mathew, Philip; Lewis, Carolyn; Munsif, Anand N; Saksena, Sanjeev (Journal of interventional cardiac electrophysiology, 1997)
The clinical efficacy of electrical algorithms for termination of slow ventricular tachycardia (VT) and ventricular fibrillation (VF) in implantable cardioverter-defibrillators (ICDs) is well established. Such algorithms have not been equally well defined for fast VT reversion. We report the testing of a prospectively designed algorithm for ICDs to treat fast VT that is inherently less responsive to antitachycardia pacing than slow VT. Fourth-generation ICD devices were programmed to three prospectively defined tachycardia detection zones as follows: cycle lengths < or = 260 ms for VF, 270-330 ms for fast VT, and > 330 ms for slow VT. The initial selected therapy for the VF zone was a high-energy biphasic shock (> 15 J), while a 3- or 5-J biphasic shock was usually administered for fast VT, and antitachycardia pacing was initially attempted for slow VT. Initial therapy was followed by backup therapy with high-energy shocks. Twenty-eight patients, 24 of whom were males, all with organic heart disease, with a mean age of 65 +/- 9 years, received either a Medtronic 7219D (23 patients), 7219C (2 patients), 7218SP1 (2 patients), or 7218C (1 patient) ICD with a nonthoracotomy lead system. The defibrillation threshold was 10 +/- 5 J. At predischarge electrophysiologic testing, a single 3- or 5-J shock terminated all episodes of fast VT tested. During a follow-up of 18 +/- 9 months, there were four nonarrhythmic deaths. Fourteen patients (50%) had a total of 21 VF, 44 fast VT, and 202 slow VT episodes. Twenty-three of 24 (96%) VF, 33 of 39 (84%) fast VT, and 193 of 202 (95.5%) slow VT episodes were terminated with the first delivered therapy in each therapy algorithm (p = NS). The overall efficacy of the entire electrical therapy algorithm was 100% for VF, 100% for fast VT, and 98% for slow VT episodes (p = NS). No patient experienced syncope or presyncope during fast VT or VF in this study. We conclude that a third detection and therapy zone can be successfully programmed in ICDs to define a range of fast VT episodes that can be effectively terminated with lower energy cardioversion shocks with comparable success and freedom from arrhythmic symptoms to electrical therapies used for slow VT and VF.